2021
DOI: 10.3389/fcell.2021.634607
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome: A Promising Therapeutic Target for Drug-Induced Toxicity

Abstract: Drug-induced toxicity, which impairs human organ function, is a serious problem during drug development that hinders the clinical use of many marketed drugs, and the underlying mechanisms are complicated. As a sensor of infections and external stimuli, nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing 3 (NLRP3) inflammasome plays a key role in the pathological process of various diseases. In this review, we specifically focused on the role of NLRP3 inflammasome in dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 206 publications
(253 reference statements)
1
15
0
Order By: Relevance
“…60, NO. 1 (21)(22)(23). Here, we reported that NLRP3 inflammasome was activated in LPS-treated HK2 cells, which was consistent with previous studies (24,25).…”
Section: Discussionsupporting
confidence: 91%
“…60, NO. 1 (21)(22)(23). Here, we reported that NLRP3 inflammasome was activated in LPS-treated HK2 cells, which was consistent with previous studies (24,25).…”
Section: Discussionsupporting
confidence: 91%
“…Apart from cGAS/STING activation, responsible for the inflammatory response, the Ox-mtDNA released via PTP-VDAC channel promotes NLRP3 inflammasome, triggering its assembly in the cytosol. During the NLRP3 inflammasome activation by oligomerization mechanisms, which occur in response to an array of Ox-mtDNA fragments, the Cas-1-mediated cleavage of proinflammatory cytokines, such as interleukin 1β (IL-1β) and interleukin 18 (IL-18), into their mature active forms is triggered [ 55 , 77 ] ( Figure 3 ).…”
Section: Mitochondria Are Potentially a New Target Of Natural Compoun...mentioning
confidence: 99%
“…In the last 20 years, several inflammasomes have been identified [ 38 ]; however, the currently most characterized one is the NLRP3 (NOD-like receptor protein 3) intracellular inflammasome, which belongs to the NOD-like receptor (NLR) family. It is activated in response to several signals and plays an important role in inflammatory diseases, autoimmune diseases, metabolic diseases (metabolic syndrome, obesity, diabetes, and gout), cardiovascular diseases, neurodegenerative diseases (Parkinson’s and Alzheimer’s disease), multiple sclerosis, and also in psychiatric diseases [ 39 , 40 , 41 , 42 ].…”
Section: Autoinflammatory Disease: Since the Beginning Of ’90s A New Branch Of Medicinementioning
confidence: 99%